Dorsal Raphe Dual Serotonin-Glutamate Neurons Drive Reward by Establishing Excitatory Synapses on VTA Mesoaccumbens Dopamine Neurons - Hui-Ling Wang; Shiliang Zhang; Jia Qi; Huikun Wang; Roger Cachope; Carlos A. Mejias-Aponte; Jorge A. Gomez; Gabriel E. Mateo-Semidey; Gerard M.J. Beaudoin; Carlos A. Paladini; Joseph F. Cheer; Marisela Morales (Cell Reports, 2019)
Summary: Dorsal raphe (DR) serotonin neurons provide a major input to the ventral tegmental area (VTA). Here, we show that DR serotonin transporter (SERT) neurons establish both asymmetric and symmetric synapses on VTA dopamine neurons, but most of these synapses are asymmetric. Moreover, the DR-SERT terminals making asymmetric synapses on VTA dopamine neurons coexpress vesicular glutamate transporter 3 (VGluT3; transporter for accumulation of glutamate for its synaptic release), suggesting the excitatory nature of these synapses. VTA photoactivation of DR-SERT fibers promotes conditioned place preference, elicits excitatory currents on mesoaccumbens dopamine neurons, increases their firing, and evokes dopamine release in nucleus accumbens. These effects are blocked by VTA inactivation of glutamate and serotonin receptors, supporting the idea of glutamate release in VTA from dual DR SERT-VGluT3 inputs. Our findings suggest a path-specific input from DR serotonergic neurons to VTA that promotes reward by the release of glutamate and activation of mesoaccumbens dopamine neurons. : Wang et al. identify the ultrastructural and molecular characteristics of synaptic connectivity between DR serotonin neurons and VTA dopamine neurons and determined the role of these connections in behavior. Their results indicate that the DR→VTA serotonergic neurons promote reward by the co-release of glutamate and activation of mesoaccumbens dopamine neurons. Keywords: dorsal raphe nucleus, ventral tegmental area, serotonin, VGluT3, reward